Identifikasi Tanaman Jahe-Jahean (Famili Zingiberaceae) di Bali yang dapat Dimasukkan Sebagai Elemen dalam Desain Lanskap - PUTRA, I GUSTI NGURAH MANIK SEDANA; SUKEWIJAYA, I MADE; PRADNYAWATHI, NI LUH MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
Normal 0 false false false EN-US X-NONE X-NONE ABSTRACT Identification of the Ginger Plant (Famili y of Zingiberaceae) in Bali, as an Element in Landscape Design Ginger plants (Family Zingiberaceae) wellgrow in most regions in Indonesia, including Bali. Beside as a medicinal plants, the plant is also currently used as an element in design of landscape. Objectives of the research were: 1) inventory and identify plants of Zingiberaceae family found in bali; 2) to group those plant in to the specific element of landscape design according to their heght, color and texture; 3) to find out the level of preferences of people to those plant. Method use in reseach were a survey method and organoleptic test. Data were collected from eight regencies and one city in Bali throught a survey. Organoleptic test was done 30 respondents, including 10 peoples who expert in landscape design. The result of the survey investigated 35 speciments of grown in Bali. Those spesiments were identified and grouped in to 9 genera, i. e. Alpinia, Amomum, Boesenbergia, Curcuma, Eletaria, Etlingera, Hedychium, Kaempferia , and Zingiber . Regarding, to group in to specific element of landscape design, plant are grouped into: size (6 tall shrubs, 18 medium shrubs, 8 low shrubs and 1 ground cover), colour (21 flower, 8 leaf varian color) and texture (8 coarse, 19 medium and 5 smooth). Organoleptik test showed that flowers that have bright colour and varied in shape were the most favoured by respondents. However, species of Kaempferia galanga had highest level of preference by respondents on the shape and colour of plant in a whole. While, leaf that have combination of the colour and taper leaf shape were the most favoured by respondents. Keyword : identification, Zingiberaceae, landscape design